1954
DOI: 10.3133/pp260e
|View full text |Cite
|
Sign up to set email alerts
|

Bikini and nearby atolls, Marshall Islands; oceanography (biologic) : Biologic economy of coral reefs

Abstract: The eastern reefs of Rongelap Atoll, composed of animals and attached algae, produce more organic matter than they consume. The productivity per unit area is considerably higher than that of adjacent waters or any^other open marine areas. The zooxanthellae of the corals make a substantial contribution to the whole production, so that per unit of weight, actively growing reef corals may photosynthesize as fast as lithothamnia Review of work on other coral reefs indicates that these communities are generally sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1957
1957
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Because the water of this area is constantly interchanged with the sea beyond, however; its hydrologic variations involve only slight changes in depth and chemistry and a somewhat wider temperature fluctuation. The organic productivity, chemical nutrients, and oxygen balance of parts of the Great Barrier Keef waters (Orr, 1933;Orr and Moorhouse, 1933) and of the Marshall Islands reefs and lagoons (Sargent and Austin, 1954) have been discussed and compared with other reef complexes in a way that suggests broad similarity in these features between reef-encircled waters. Orr (1933, p. 50-52) emphasizes the very slight year-round variation in phosphate and nitrate content of the Great Barrier Reef waters, resulting in absence of phytoplankton blooms but year-round steady numbers.…”
Section: The Barrier Reef Lagoon and Contiguous Fringing Reef Moatsmentioning
confidence: 99%
“…Because the water of this area is constantly interchanged with the sea beyond, however; its hydrologic variations involve only slight changes in depth and chemistry and a somewhat wider temperature fluctuation. The organic productivity, chemical nutrients, and oxygen balance of parts of the Great Barrier Keef waters (Orr, 1933;Orr and Moorhouse, 1933) and of the Marshall Islands reefs and lagoons (Sargent and Austin, 1954) have been discussed and compared with other reef complexes in a way that suggests broad similarity in these features between reef-encircled waters. Orr (1933, p. 50-52) emphasizes the very slight year-round variation in phosphate and nitrate content of the Great Barrier Reef waters, resulting in absence of phytoplankton blooms but year-round steady numbers.…”
Section: The Barrier Reef Lagoon and Contiguous Fringing Reef Moatsmentioning
confidence: 99%
“…Waters adjacent to coral reefs and seagrass beds show variations at a range of temporal scales (from hours to years). Diurnal changes in NEP and NEC and associated changes in pH, dissolved oxygen (DO), and partial pressure of CO 2 (pCO 2 ) of waters adjacent to coral reef organisms were first measured more than 60 yr ago (Seargent & Austin 1954, Odum & Odum 1955, Smith 1973). More recently, these variations have been further described by several others (Kayanne et al 2005, Yates & Halley 2006, Manzello 2010, Anthony et al 2011, Kleypas et al 2011, McGillis et al 2011, Santos et al 2011, Gray et al 2012, Price et al 2012, Smith et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…But corals and other animals flourish as well on seaward slopes as behind reefs where the supposed food supply is much larger. On the assumption that oxygen production and consumption on a reef tract is a measure of organic productivity, Sargent and Austin (1954) found that productivity from unit areas on reefs is higher than in the waters of the open sea around them, and that reefs appear to be self-sustaining organic structures. They suggest that this is due in large part to the greater efficiency of the zooxanthellae and other fixed algae compared to planktonic algae.…”
mentioning
confidence: 99%